A Review on the Elemental and Isotopic Geochemistry of Gallium. Issue 9 (26th September 2021) - Yuan, Wei; Chen, JiuBin; Teng, Henry; Chetelat, Benjamin; Cai, Hongming; Liu, Jincun; Wang, Zaicong; Bouchez, Julien; Moynier, Frederic; Gaillardet, Jérôme; Schott, Jacques; Liu, Congqiang
Abstract: Gallium exhibits weak metallic properties owing to its proximity to non‐metals in the periodic table, yet is volatile in extra‐terrestrial bodies and fairly reactive in nature. It has been used extensively to elucidate the Solar System evolution, planet interior differentiation, and terrestrial processes. However, Ga speciation and transformation in various planetary compartments and the dynamics of its trans‐reservoir pathways remain to be fully resolved. Although recent studies and the development of modern analytical techniques for Ga isotopes have markedly improved our understanding of Ga geochemistry, a systematical summary of state‐of‐the‐art knowledge appears to be long overdue. Here we provide an overview of the geochemical properties of Ga in different reservoirs, including meteorites and Earth's interior and exterior compartments, and a timely review of Ga isotopic geochemistry. We also provide a first tentative estimate of total masses of Ga in different compartments and the trans‐reservoir Ga flux, based on the published data. This compilation reveals clearly the lack of geochemistry data of Ga in Earth's interior, the imbalance of oceanic Ga budget and the potential implications of Ga isotopes, stimulating future systematic studies of Ga and its isotopes in geosciences and related fields. Abstract :